2023
DOI: 10.3390/ani13061059
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Protective Properties of Lactic Acid Bacteria Intended to Be Used in Probiotic Preparation for Honeybees (Apis mellifera L.)—An In Vitro Study

Abstract: Lactic acid bacteria (LAB) are widely used probiotics and offer promising prospects for increasing the viability of honeybees. Thus, the probiotic potential of 10 LAB strains was determined, which in our previous studies showed the most potent protective abilities. In the current study, we investigated various properties of probiotic candidates. The tested LAB strains varied in susceptibility to tested antibiotics. Isolates showed high viability in sugar syrups and gastrointestinal conditions. None of the LAB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 123 publications
(185 reference statements)
0
7
0
Order By: Relevance
“…The absence of antagonistic interactions among these strains is promising for their inclusion in a honeybee probiotic supplement, fostering a stable and effective multi-strain product. Few studies have investigated the antagonistic effects of LAB strains intended for probiotics in bees [ 49 , 71 ]. This study supports the use of LAB combinations to enhance honeybee health and resilience.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The absence of antagonistic interactions among these strains is promising for their inclusion in a honeybee probiotic supplement, fostering a stable and effective multi-strain product. Few studies have investigated the antagonistic effects of LAB strains intended for probiotics in bees [ 49 , 71 ]. This study supports the use of LAB combinations to enhance honeybee health and resilience.…”
Section: Discussionmentioning
confidence: 99%
“…This aligns with previous findings [ 76 , 77 ], which suggest that lactobacilli may benefit from osmotic protection in the presence of sucrose, thereby contributing to better survival and highlighting the impact of syrup composition on the survival rates of LAB strains. Additionally, Iorizzo et al [ 78 ] noted that A. kunkeei strains isolated from the digestive tract of honeybees showed tolerance to high sugar concentrations, while Leska et al [ 49 ] tested the viability of ten isolated LAB strains and one reference strain, A. kunkeei DSM 12361, in syrups of varying concentrations of glucose, fructose, or sucrose, and the reported results showed a better survival rate of LAB in the syrup with glucose and fructose without sucrose. In this study, the best survival rates for LAB were observed in syrups with carbohydrate concentrations below 55% for both tested syrups, suggesting commercial syrups might need dilution before being used to administer the probiotic mix.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lactobacillus plantarum , with its robust fermentative ability and adaptability to different substrates, has been documented to improve the digestibility and nutritional profile of various foods. The fermentation process with L. plantarum and L. acidophilus not only breaks down complex food matrices but also potentially increases the levels of essential amino acids, vitamins, and bioactive peptides, adding to the functional value of BP [ 21 , 22 , 23 , 24 , 25 ]. One of the notable benefits of L. plantarum in fermentation is its capacity to improve the bioavailability of nutrients.…”
Section: Introductionmentioning
confidence: 99%